Developing a B2B online communicating plan : A case study of WAX project - Kauppinen, Tuukka; Minh, Le (2018)
As a part of WAX project, this report was written to look for different viewpoints in terms of communicating with multiple B2B targeted groups. Funded by Interegg Nord, WAX project is a collaboration between University of Oulu, Luleå Technical University, NIBIO - Norwegian Institute of Bio-economy Research and OAMK - Oulu University of Applied Sciences. WAX project aims to make contacts with scientist, researchers, investors and possible B2B buyers. Raising awareness of the product, funds and practicable partnerships can help advancing its potential even more. Seeing the rising demand of wax-based products and the untapped availability of berries as main resource, WAX project wants to send a message to interested parties about an alternative solution – extracting wax from arctic berries, which can result in many benefits. This thesis includes graphic design elements, mostly in .AI and .PSD formats. Such as, website template, logo, article template, slides, etc.